Grenzüberschreitungen. Migration. Entterritorialisierung des - Jestaedt, Matthias (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2017)
This volume includes lectures and discussion from the Conference of the Association of German Professors of Constitutional Law in Linz, 5&#82118 October 2016